PENGARUH PENGGUNAAN APLIKASI WORDWALL TERHADAP PEMAHAMAN KONSEP BANGUN DATAR SISWA KELAS V SD MUHAMMADIYAH PERUMNAS - Tasyah, Hamdani; Andi Husniati; Andi Alim Syahri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using the Wordwall application in improving the understanding of fifth-grade students at SD Muhammadiyah Perumnas regarding the concept of plane geometry. The research employed a quantitative pre-experimental approach with a one-group pre-test and post-test design involving 20 students. Data analysis was conducted using a paired sample t-test and N-gain score calculation. The results showed that the average pre-test score of 25.70 increased significantly to 88.45 in the post-test. The paired sample t-test indicated a significance value of 0.000, which is lower than 0.05, meaning that there is a significant difference between the results before and after the treatment.